Group-based trajectory analysis of acute pain after spine surgery and risk factors for rebound pain - Li, Yi-Shiuan; Chang, Kuang-Yi; Lin, Shih-Pin; Chang, Ming-Chau; Chang, Wen-Kuei (Frontiers in Medicine, 2022)
Background: The current study aimed to investigate the patterns of postoperative pain trajectories and their influential factors in patients receiving spine surgery and intravenous patient-controlled analgesia (IVPCA). Methods: This retrospective study was conducted in a tertiary medical center and included patients undergoing spine surgery with IVPCA for postoperative pain control between 2016 and 2018. Maximal pain intensity was collected daily during the first postoperative week. Group-based trajectory analysis was performed to categorize the variation in pain intensity over time and identify predictors of rebound pain after the end of IVPCA. The associations between the pain trajectory classification and amount of IVPCA consumption or length of hospital stay after surgery were also evaluated. Results: A total of 547 patients with 3761 pain scores was included in the analyses and two postoperative pain trajectory groups were identified: Group 1 with mild pain trajectory (87.39%) and Group 2 with rebound pain trajectory (12.61%). Risk factors of the rebound pain trajectory were age less than 65(OR: 1.89; 95% CI: 1.12 – 3.20), female (OR: 2.28; 95% CI: 1.24 – 4.19), and moderate to severe pain noted immediately after surgery (OR: 3.44; 95% CI: 1.65 – 7.15). Group 2 also had more morphine consumption (p < 0.001) and longer length of hospital stay (p < 0.001) than Group 1. Conclusion: Group-based trajectory analysis of postoperative pain provides insight into the patterns of pain resolution and helps identify unusual courses. More aggressive pain control strategies should be considered in patients with high risk for rebound pain after the end of IVPCA for spine surgery.